Taxonomic review of Palearctic Eurypogon Motschulsky (Coleoptera: Artematopodidae), with a redescription of the only European species and descriptions of three new species from China - Packova, Gabriela; Hájek, Jiří; Geiser, Michael; Kundrata, Robin (Zootaxa, 2024)
Eurypogon Motschulsky, 1860 is a small genus in the beetle family Artematopodidae distributed in the Holarctic region. Here, we review the Palearctic members of this genus, with main emphasis on the dark-colored species. We redescribe E. cribratus (Hampe, 1867) from Italy and describe three new species from China: E. pubescens sp. nov. from Shaanxi province, E. ruzickai sp. nov. from Yunnan province, and E. turnai sp. nov. from Hubei province. This brings the total number of Eurypogon species to 16. Additionally, we provide morphological diagnoses and photographs of selected characters for all previously described East Palearctic species as well as an updated identification key for the species of mainland China. We discuss the variability of main diagnostic characters, including the shape of pronotum, the surface and punctation of elytra, and the shape of male genitalia.